2005
DOI: 10.1177/0092055x0503300402
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Successful International Distance-Learning Classroom

Abstract: As the global economy becomes more integrated, incorporating international experiences into college curricula becomes increasingly desirable for American students and their counterparts abroad. This paper describes one model for creating an international, Web-based, distance-learning classroom that can be used as a guide for those who might wish to pursue similar endeavors. Our replicated experiences teaching a sociology course on social control, twice under slightly different conditions, provide the basis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…Online discussion forums have been widely used in distance education for some time (Curran et al, 2003; Little et al, 2005). However, teacher moderated online discussions have become a common educational tool used more broadly in higher education (Vlachopoulos and Cowan, 2010), particularly in blended learning education models as an adjunct to traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Online discussion forums have been widely used in distance education for some time (Curran et al, 2003; Little et al, 2005). However, teacher moderated online discussions have become a common educational tool used more broadly in higher education (Vlachopoulos and Cowan, 2010), particularly in blended learning education models as an adjunct to traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Where courses are taught across multiple campuses this blended delivery model incorporating the use of discussion forums has been used as a method of providing equality of learning experience across all campuses (Anderson and Date‐Huxtable, 2011). The use of online discussion forums has been reported across a variety of disciplines including education (Jin, 2005; Son, 2006; Wade et al, 2008), social sciences (Little et al, 2005), sciences (Missett et al, 2010), medicine (Curran et al, 2003), and the health sciences more generally (Ellenchild Pinch and Graves, 2000; Buckley et al, 2005; Thomas and Storr, 2005; Wharrad et al, 2005) but it is only very recently that such forums have been reported for anatomy teaching (Choudhury and Gouldsborough, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social science orientation of the class is sufficiently similar to the previous research settings that provided a basis for our hypothesis (cf. Howard, 2005;Koeber, 2005;Little, Titarenko, & Bergelson, 2005;Clark-Ibáñez & Scott, 2008;Koeber & Wright, 2008;Hill, Arford, Lubitow, & Smollin, 2012;Hoop, 2012). Content related to American government, associated social structures, and individual behavior clearly has potential fodder for student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Online education is not only about having access to the Internet, but also about how connection to the Internet is embedded in social relations in the students' daily life (Rye, 2007). As Beer (2005) Handling diversity in cultural backgrounds to create a successful online learning environment is another issue discussed in the literature (Bates, 1999;Bates & de los Santos, 1997;Little, Titarenko, & Bergelson, 2005;Rasmussen, 2006;Williams et al, 2001). A focus in this literature has been on how to facilitate collaboration despite language barriers and across a variety of educational cultures.…”
Section: The Importance Of the Local Context In Online Distance Educamentioning
confidence: 99%